MARKET BASKET ANALYSIS PADA RM. DAPOER KERANG MENGGUNAKAN ALGORITMA APRIORI - Razaq, Jeffri Alfa; Astutik, Yuny (Information Technology and Telematics, 2019)
ABSTRACT Dapoer Kerang Restaurant is a restaurant that has several menu variants made from processed seafood located at Jl. Suyudono No.68, Bulustalan, Semarang City. Of the various menu variants that are sold, business owners have difficulty in making effective sales strategies. Business owners need a linkage picture between menus sold based on the relationship pattern of ordering one menu with other menus by consumers that are purchased simultaneously. The implementation of market basket analysis at Dapoer Kerang Restaurant using a priori algorithm can help in the process of analyzing the purchase menu of food menus to find a menu purchase pattern that is often purchased together to develop marketing strategies in sales at Dapoer Kerang Restaurant. To support the analysis process, understanding and processing data in data preparation using the CRISP-DM (Cross Industry Standard Process for Data Mining) method. The results of this analysis are in the form of association rules that can be used by business owners as a reference in developing marketing strategies at Dapoer Kerang Restaurant.